Pilot Study of Psychological Conditions Volunteer Disaster Covid 19 - Ike Mardiati Agustin; Nurlaila Nurlaila; Hendri Tamara Yuda; Yulia Yulia (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Pandemic Covid 19 is a non-natural disaster that raise various problems for all levels of society. This disaster condition will provide various physical and psychological impacts for each individual including the volunteers of this non-natural disaster. Volunteers are vulnerable groups, need to be identified psychological conditions in each of their assignments. Based on this phenomenon, it is interesting to see a preliminary study of the psychological conditions of volunteers disaster covid 19. The purpose of this study was to determine the psychological condition of volunteers disaster covid 19 in Kebumen Regency. This research method is descriptive analytic on 72 covid 19 volunteers which is a combination of Kebumen regional disaster management department and STIKES Muhammadiyah Gombong disaster volunteers, the sampling process is taken with simple random sampling, the psychological conditions of volunteers measured using the DASS (Depression Anxiety Stress Scale) Instrument. The results of this study obtained a psychological picture of covid 19 volunteers namely 69 people (95.83%) experienced mild anxiety and 1 person (1.39), 69 people (95.83%) experienced mild depression, and 69 people (95, 83%) experience mild stress. This research is recommended as a preliminary study which is the basis for conducting an ongoing program for psychological strengthening of disaster volunteers.